PELATIHAN PENJUALAN BERBASIS ONLINE UNTUK PENINGKATAN PENDAPATAN USAHA MIKRO KECIL MENENGAH MASYARAKAT YANG TERDAMPAK COVID-19 DI KELURAHAN ANDUONOHU KECAMATAN POASIA KOTA KENDARI - Husin; Erwin Hadi Santoso; Nasrullah Dali; Tuti Dharmawati; Fitriaman; Safaruddin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
This activity involves direct interaction which will provide opportunities for Micro, Small and Medium Enterprises in Anduonohu ​​Village, Poasia District to increase income. The output of this activity is the formation of a good and correct income calculation model using technology in developing its business and producing products that can meet legal, economic and social impact aspects. As well as being able to start implementing online sales and making packaging to make it more attractive. Forming groups of Micro, Small and Medium Enterprises, especially in Anduonohu ​​Village that can practice online-based sales of the products they produce and are able to develop packaging innovations to make them more attractive to consumers.